2006
DOI: 10.1111/j.1360-0443.2006.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of childhood risk factors in initiation of alcohol use and progression to alcohol dependence

Abstract: Results highlight the role of psychiatric and substance use disorders in progression from first drink to AD, underscore the continuity of risk associated with CD and indicate that (with the exception of CD) different factors play a role in transition to AD than in initiation of alcohol use. Distinctions between stages are interpreted in a developmental framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
233
4
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(270 citation statements)
references
References 68 publications
23
233
4
10
Order By: Relevance
“…Elucidation of the genes that contribute to smoking (46) and alcohol drinking (47)(48)(49) initiation is critical for disentangling the full etiology of development of these disorders. Furthermore, it is possible that initiation of smoking and drinking may be part of a broader spectrum of phenotypes that includes a vulnerability to developing behavioral problems (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of the genes that contribute to smoking (46) and alcohol drinking (47)(48)(49) initiation is critical for disentangling the full etiology of development of these disorders. Furthermore, it is possible that initiation of smoking and drinking may be part of a broader spectrum of phenotypes that includes a vulnerability to developing behavioral problems (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…De esta manera un tratamiento del TDAH podría prevenir el desarrollo de trastorno disocial y adicción al alcohol (Sartor et al, 2007;Tuithof, Ten Have, van den Brink, Vollebergh y de Graaf, 2011).…”
Section: Adhd and Depressant Substance Useunclassified
“…In this way, it is emphasized that psychiatric comorbidity and other SUDs play an important role as determining risk factors for the development of alcohol dependence (Sartor, Lynskey, Heath, Jacob, & True, 2007). In another two studies, it has also been reported that alcohol dependent patients who have a comorbid ADHD are characterized by early initiation of addiction (Ercan, Coskunol, Varan, & Toksoz, 2003;Sartor, Lynskey, Heath, Jacob, & True, 2007;Sringeri, Rajkumar, Muralidharan, Chandrashekar, & Benegal, 2008).…”
Section: Adhd and Depressant Substance Usementioning
confidence: 99%
See 2 more Smart Citations